Perancangan Prosedur Mutu dengan Pendekatan Penilaian Risiko - Prayogo Pangestu Subagio; Kriswanto Widiawan (Jurnal Titra, 2018)
PT. Bondi Syad Mulia is a hot dip galvanizing company. The company would like to upgrade the quality management system of ISO 9001: 2008 to ISO 9001: 2015. The upgrading of ISO 9001: 2008 to ISO 9001: 2015 is done due to the ISO 9001: 2015 expiration on 2018 and the customer’s requirements of ISO 9001:2015 for quality assurance services. Risk management tools used Risk Assessment Matrix (RAM). RAM was distributed to nine departments. The departments that received the RAM questionnaire were the galvanic department, warehouse department, purchasing department, document control department, quality control department, representative management department, human resource development department, marketing department, and mechanics department. The results of questionnaire data processing were 5 medium and large risk hazards of 76 evaluated risks. After the design of quality procedures against these 5 risks, small risk hazard level will be obtained.